(untitled) (Higher Education Politics and Economics, 2026)
This study examines the implications of the exemption to Title IX’s prohibition on sex discrimination in undergraduate admissions at private institutions. Institutional data from 2019 and 2022 were analyzed to assess patterns in admissions outcomes. The results indicate that highly selective private colleges were more frequently associated with admission advantages for men. Across both public and private institutions, applicant pools with relatively larger proportions of women were generally associated with higher admission rates for men. In contrast, institutions reporting higher proportions of enrolled women were more frequently associated with favorable admissions outcomes for women. These results motivate further research on this topic using student‑level admissions data to better assess whether such patterns reflect systematic differences among applicants or potential bias.